As estratégias de marketing global adotadas nos processos de internacionalização de franquias brasileiras - Camargo, Maria Adriana de Andrade (2012)
This study proposes an analysis of the process of internationalization of Brazilian franchises. The discussion is bounded by the influence of global marketing strategies adopted by franchises in their processes of surveyed internationalization. The goal is to identify the strategies used by the marketing departments of franchises and interprets their influence in their internationalization process. In addition, they intend to verify what were the decisions made by marketing managers and global marketing strategies (GMS) and the results obtained after the internationalization process. The theoretical frame of reference is based on studies on internationalization of enterprises internationalization of franchises and global marketing. By means of a survey of the field, using the multiple case study method, developed empirical part of work analyzing three Brazilian franchises that experienced the process of internationalization. It was realized as a result that the Brazilian franchises are on the way to the standardization of your marketing mix, but are still far from direct their business actions for the last four GMS dimensions: concentration and coordination of marketing activities,integration of competitive movements and participation in the global market. The studybreaks new ground by using GMS in the analysis and interpretation of the process ofinternationalization of Brazilian franchises, and by using the software IT Atlas as a tool for content analysis in the preparation of cases.